Elevated Systemic and Parasite—Antigen Stimulated Levels of Type III IFNs in a Chronic Helminth Infection and Reversal Following Anthelmintic Treatment - Rajamanickam, Anuradha; Munisankar, Saravanan; Bhootra, Yukthi; Dolla, Chandrakumar; Nutman, Thomas B.; Babu, Subash (Frontiers in Immunology, 2018)
Type III IFNs are important players in immunity to viral and bacterial infections. However, their association with helminth infections has not been examined. To explore the association of Type III IFNs with Strongyloides stercoralis (Ss) infection, we examined the systemic levels of IFN lambda-1, IFN lambda-2 and IFN lambda-3, IL-10, and CXCL10/IP-10 in Ss infected (INF, n = 44), helminth—uninfected (UN, n = 44) and in post-treatment INF individuals. We also examined the levels of IFN lambda-1, IFN lambda-2 and IFN lambda-3, IL-10, and CXCL10/IP-10 in whole blood culture supernatants stimulated with Ss somatic antigens, or PPD or LPS. Finally, we performed correlations of systemic Type III IFN levels with absolute numbers of dendritic cell subsets. Ss infection is characterized by elevated systemic levels of IFN lambda-1, IFN lambda-2 and IFN lambda-3, IL-10, and CXCL10/IP-10 in comparison to UN individuals and a significant reduction following anthelmintic treatment. Ss infection is also characterized by elevated levels of unstimulated or Ss antigen stimulated levels of IFN lambda-1, IFN lambda-2 and IFN lambda-3, CXCL10/IP-10 and a significant reduction following treatment. In addition, Ss infection is characterized by increased numbers of plasmacytoid and myeloid dendritic cells in comparison to UN individuals, with a significant reduction following anthelmintic treatment of INF individuals. Finally, Ss infection exhibits a significant positive correlation between the systemic levels of IFN lambda-2 and IFN lambda-3 and the numbers of plasmacytoid dendritic cells. Thus, Ss infection is characterized by elevations in systemic and antigen—induced levels of Type III IFNs, which is positively associated with the numbers of plasmacytoid dendritic cells and reversed upon anthelmintic treatment.